A molecular timer couples organism-wide temporal identity to developmental checkpoints - Peipei Wu; Jing Wang; Brett Pryor; Isabella Valentino; David F. Ritter; Kaiser Loel; Olya Yarychkivska; Shai Shaham; Justin Kinney; Sevinc Ercan; Leemor Joshua-Tor; Christopher M. Hammell (Proceedings of the National Academy of Sciences, 2026)
Coordinated development requires that growth and cell-fate transitions occur in a defined temporal order across tissues, yet how multicellular organisms generate and synchronize developmental timing information remains unclear. In Caenorhabditis elegans , stage-specific cell-fate transitions are driven by pulsatile transcription of microRNAs, including lin-4 and let-7 family members, but the mechanism that produces these rhythms has been unknown. Here, we identify a developmental timer composed of the transcription factor MYRF-1 and the PERIOD-like repressor LIN-42 that operates synchronously across all somatic tissues. MYRF-1 binds conserved regulatory elements upstream of heterochronic microRNA genes and drives once-per-stage transcriptional pulses that are phase-locked across tissues, while simultaneously activating lin-42 expression. Newly synthesized LIN-42 directly associates with MYRF-1, limiting its nuclear residence and transcriptional activity and thereby constraining the amplitude and duration of each pulse. Beyond regulating stage-specific gene expression, we show that MYRF-1 activity is also required to license a developmental checkpoint essential for growth and successful ecdysis. Together, these findings define a reciprocal transcriptional–translational feedback loop that generates organism-wide developmental timing information, coupling tissue-specific differentiation programs to coordinated organismal growth through a shared molecular timer.